Regression I. Experimental Approaches to Regression - Alexandrov, Yuri I.; Svarnik, Olga; Znamenskaya, Irina; Kolbeneva, Marina; Arutyunova, Karina R.; Krylov, Andrey; Bulava, Alexandra I.; Feldman, Brian (Journal of analytical psychology, 2020)
The concept of regression is considered with an emphasis on the differences between the positions of Freud and Jung regarding its significance. The paper discusses the results of experimental analyses of individual experience dynamics (from gene expression changes and impulse neuronal activity in animals to prosocial behaviour in healthy humans at different ages, and humans in chronic pain) in those situations where regression occurs: stress, disease, learning, highly emotional states and alcohol intoxication. Common mechanisms of regression in all these situations are proposed. The mechanisms of regression can be described as reversible dedifferentiation, which is understood as a relative increase of the representation of low-differentiated (older) systems in the actualized experience. In all of the cases of dedifferentiation mentioned above, the complexity of the systemic organization of behaviour significantly decreases.